Banyumasan Songs As Banyumas Peopleâs Character Reflection - Suharto, S. (Department of Drama, Dance, and Musik (Sendratasik), Semarang State University, 2016)
This study aims to identify a number of legendary Banyumasan songs. The fact that a large number of the songs exist and people sing the songs all the time shows that the songs have their own uniqueness. This study takes place in Banyumas regency. By doing performance study and composition, this study identifies the form and the structure of Banyumasan songs, and the moral value of Banyumasan music, especially the songs in Banyumasan music. The result of the study shows that the songs in the art performances in Banyumas commonly use classic immutable songs. The lyrics in the classic Banyumasan songs use Ngoko Javanese in Banyumasan dialect. The rhyme of the lyrics is usually in the form of wangsalan, parikan, and Essen-Essen. The rhyme contains funny and entertaining riddles. The lyrics of Banyumasan songs reflect Banyumas peopleâs character and the dream/utopia of the peopleâs ideology. The character is shown in the use of ngoko Javanese in Banyumas dialect which shows that the society is blakasuta or egalitarian who considers all people in the world has the same level and must be honest.How to Cite: Suharto, S. (2016). Banyumasan Songs As Banyumas Peopleâs Character Reflection. Harmonia: Journal of Arts Research And Education, 16(1), 49-56. doi:http://dx.doi.org/10.15294/harmonia.v16i1.6460